Ongoing evolution of urinary tract disorders in dromedary camels (Camelus dromedarius): a comprehensive illustrated sonographic overview - Tharwat, Mohamed; Elmoghazy, Hazem M. M. (Frontiers in Veterinary Science, 2025)
In practice, urinary tract disorders are increasingly reported in dromedary camels, particularly in regions where environmental stress and limited resources prevail. Our primary goal in writing this review was to provide a simple, accessible, and practical data tailored for veterinary clinicians working with dromedary camels in remote and resource-limited environments. These veterinarians often operate under harsh conditions such as pastoral regions of North Africa, the Middle East, and parts of South Asia, with very basic tools and limited access to advanced diagnostic equipment. Therefore, we intentionally structured this manuscript to be practical and user-friendly in such settings, emphasizing clinical relevance and practicality over exhaustive academic depth. The review is structured to highlight the main urinary disorders affecting dromedary camels, with a focus on their incidence, clinical presentation, and sonographic characteristics. While not exhaustive in academic detail, this review maintains scientific accuracy with a focus on practical application. The first section discusses the incidence and trends of various urinary tract disorders observed in dromedary camels. The second section provides an overview of the ultrasonographic anatomy of the urinary system in healthy camels. The third and main section focuses on the ultrasonographic findings associated with urinary tract disorders in affected camels that contains illustrative images of published case reports as well as clinical studies. This section is further divided into seven subsections: (1) pyelonephritis and renal abscesses, (2) urinary tract calculi, (3) urine retention, dribbling, and anuria, (4) urinary bladder rupture, (5) urethral rupture, (6) cystitis, and (7) urinary neoplasia. A thorough understanding of the pathophysiology of urinary tract diseases in dromedary camels is essential for developing effective treatment and control strategies considering normal variation or age-related differences. If appropriate, the review discusses also treatment options or preventive measures based on sonographic findings. By presenting recent research findings, this review aims to raise awareness and guide future strategies for the diagnosis and management of urinary tract diseases in dromedary camels, ultimately contributing to improved health outcomes in both domestic and wild populations.